Knitting Together: The Role of Collaboration in Alleviating Poverty - Lukman, Andi (Cendekiawan Indonesia Timur, 2024)
This research explores the crucial role of collaboration in addressing the multifaceted challenge of poverty. Drawing on case studies from diverse contexts, the study examines how partnerships between governments, non-governmental organizations, private sector actors, and communities themselves can contribute to more effective and sustainable poverty alleviation efforts. The analysis highlights the synergistic effects of collaborative approaches, demonstrating how pooling resources, sharing expertise, and coordinating efforts can amplify impact and overcome the limitations of siloed interventions. The study delves into the key elements of successful collaborations, including shared vision and goals, clear roles and responsibilities, effective communication channels, and mechanisms for mutual accountability. Furthermore, it examines the specific contributions of different stakeholders, emphasizing the importance of community ownership and leadership in driving sustainable change. By showcasing successful collaborative models and distilling key lessons learned, this research aims to provide valuable insights for policymakers, development practitioners, and community leaders seeking to forge effective partnerships and weave together a stronger safety net for those experiencing poverty.